Indonesia-Timor Leste Maritime Boundaries on Exclusive Economic Zone: Equitable Principle - Dina Sunyowati; Pradnya Paramitha Putri Ariadhi; Mochamad Kevin Romadhona; Alaa Basil Baqer Alfadhel (Universitas Negeri Semarang, 2023)
The boundaries of the sea area between one country's territory affect the sovereignty in the sea territory of another country. Indonesian Sea borders several countries, both in the EEZ and on the continental shelf. However, Indonesia has not yet finalized the determination of its maritime border with Timor Leste. The undetermined maritime boundary between Indonesia and Timor Leste affects the sovereignty of Timor Leste and affects Indonesia's space for movement. The purpose of this study is to find out the provisions and principles of determining maritime boundaries between the countries of Indonesia and Timor Leste. The method in this research is normative research with a statutory approach, a case approach, and a conceptual approach. The results of this study indicate that the Government of the Republic of Indonesia in determining territorial boundaries negotiates to determine how to draw maritime boundaries between the two countries by applying equitable principles. The process of negotiating maritime boundaries between Indonesia and Timor Leste with equitable principles can be a solution thus maritime boundaries between the two countries are immediately agreed upon